Disaster preparedness for records management: a conceptual review / Fatin Nur Zulkipli - Zulkipli, Fatin Nur (Faculty of Information Management, 2021)
In this paper, the disaster preparedness for the effective management of records in the different organizations has been explored. Disaster preparedness is a part of the overall disaster management by the organization and this is done to protect the paper and electronic record from getting damage in manmade or natural disasters. This conceptual paper aims to discuss the importance of disaster preparedness for the records management. This paper also discusses the role of information and technology in enabling the organizations developing and implementing disaster management frameworks and policy which can be utilized by the staff for securing the paper-based as well as electronic records. The literature gap has been explored. A qualitative research methodology has been selected for this topic and literature shall be reviewed systematically for arriving at the answers of the research questions. Hence, this conceptual paper shall be useful for the international organization in taking steps for protecting their vital records from the disasters.